2016
DOI: 10.5812/archneurosci.28211
|View full text |Cite
|
Sign up to set email alerts
|

Effective Teaching Strategies for Patient Education in Individuals With Spinal Cord Injury in Iran

Abstract: Background: Spinal cord injury (SCI) causes multiple complications, which can be prevented or minimized, through patient education (PE). Individuals with SCI are different, according to culture, socioeconomic status, level of education, access to educational facilities, and geographic region. Therefore, different teaching strategies should be used to increase effectiveness of education. Objectives: The aim of this study is to evaluate the perspectives of individuals with SCI, about their preferred methods of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Social support includes effective training to prepare caregivers for their new role, providing educational and occupational opportunities and may be financial supports. This study corroborated that the majority of people with SCI were young men as it was implied in other similar studies in Iran 5,16,19 and other countries. 6,20 For the occupational status, we found the positive impact of the SCI individuals' employment on reducing the burden score by the caregivers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Social support includes effective training to prepare caregivers for their new role, providing educational and occupational opportunities and may be financial supports. This study corroborated that the majority of people with SCI were young men as it was implied in other similar studies in Iran 5,16,19 and other countries. 6,20 For the occupational status, we found the positive impact of the SCI individuals' employment on reducing the burden score by the caregivers.…”
Section: Discussionsupporting
confidence: 91%
“…1,2 This condition causes numerous complications, including physical difficulties such as pain, pressures, ulcer and psychological distress like depression, 3 most of which are accompanied with financial difficulties. 4,5 The SCI not only markedly impacts those with the injury, but also their family members. The individuals with SCI dependent on others for their activities of daily life in different levels, 6 and accordingly it challenges them and their families in terms of physical, social and psychological issues.…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that the preferred method of education in an Iranian population with SCI were educational movies, lectures, TV programs, brochures, online resources. 9 It is important that SCI education programs consist of active learning or contextual-based strategies and considers the different preference of patients in order better educate and prepare patients. 18,30 Limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many of these barriers can be mitigated by educating patients early and often by using different teaching strategies. 9 All patients with a SCI should undergo a thorough assessment of their needs. Patient's needs might be different across multiple societies with various cultures and socioeconomic status.…”
mentioning
confidence: 99%
“…13 SCI/D represents a lifelong condition that necessitates self-management to reduce complications and achieve a high quality of life. [14][15][16][17] Individuals with SCI/D exhibit high levels of health information seeking, [18][19][20] including frequent use of health professionals as information sources and internet use for health maintenance. 18,20,21 A cross-sectional analysis found that adoption of VHA's PHR portal among Veterans varied significantly by condition, and that Veterans with SCI/D were among the highest adopters.…”
mentioning
confidence: 99%